Assessment of mineral block that use potato starch as binder - Nabilah Aminah, Lupti; Siti Nurfadilah, A. (Malaysian Technical Universities Network (MTUN), 2011)
Organized by Malaysian Technical University Network (MTUN) consist of Universiti Teknikal Malaysia Melaka (UTeM), Universiti Malaysia Perlis (UniMAP), Universiti Malaysia Pahang (UMP) and Universiti Tun Hussein Onn Malaysia (UTHM), 28th - 29th June 2010 at Bayview Hotel, Malacca, Malaysia.